PENGELOLAAN PEMBELAJARAN BAHASA INGGRIS BIDANG KETERAMPILAN MENULIS - Usna Delfita; Rambat Nur Sasongko; Zakaria Zakaria (Manajer Pendididikan, 2017)
The objective of this research is to describe the instructional management of English in writing skill at Junior High School Number 01 South Bengkulu. The method of this research was qualitative research. The data were collected by conducting personal interview, observations and documentation study. Then, data analysis used qualitative technique. The result of this study showed that (1) in planning of learning of English writing  skill, it was done well by English teachers, (2) in teaching learning process (implementation), English teachers used various and interesting  methods and media. (3) in evaluating and supervision the learning management, teacher had found appropriate method of measuring the students’ achievement, (4) in feedback of teaching learning process was done by doing remedial and enrichment.